DINAMIKA TRAUMA PSIKOLOGIS PADA REMAJA PENYITAS ERUPSI GUNUNG MERAPI - Nur Rahmawati, Laily; Triyono, Triyono (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Indonesia is one of the countries most vulnerable to natural disasters due to its unique geographical location at the convergence of four major tectonic plates Asian, Australian, Indian Ocean, and Pacific and the presence of the Pacific Ring of Fire. One of the most active volcanoes in the region is Mount Merapi, which has a long history of eruptions, including significant events in 2010, 2016, and 2018. Balerante Village in Kemalang District, Klaten Regency, is among the high-risk zones frequently affected by Merapi’s eruptions. The residents, including adolescents, often face repeated evacuations and severe disruptions to their daily lives. These experiences pose serious psychological challenges, particularly in the form of trauma. This study explores the psychological trauma experienced by adolescent survivors of Mount Merapi’s eruptions in Balerante Village. Using a qualitative research method with a phenomenological approach, the study involved three participants who were selected based on PTSD screening results. Data were collected through in-depth interviews and analyzed through coding and thematic interpretation. The findings reveal that all participants experienced significant traumatic effects, including flashbacks, avoidance behavior, anxiety, and varying perceptions of the disaster. While some showed resilience and readiness for future disasters, others expressed fear and a desire to relocate. Family support emerged as a key factor in psychological recovery, helping participants manage their emotional responses and develop adaptive coping strategies. This study highlights the importance of mental health interventions and family-based support systems in disaster-prone areas. ABSTRAK Indonesia merupakan negara yang sangat rentan terhadap bencana alam, khususnya erupsi gunung berapi, akibat letak geografisnya yang berada di pertemuan empat lempeng tektonik dan berada pada jalur Cincin Api Pasifik. Salah satu wilayah yang paling terdampak adalah Desa Balerante di lereng tenggara Gunung Merapi, yang termasuk dalam Kawasan Rawan Bencana III (KRB III). Penelitian ini bertujuan untuk mengeksplorasi dinamika trauma psikologis pada remaja penyintas erupsi Gunung Merapi dengan menggunakan pendekatan kualitatif fenomenologis. Tiga orang remaja dipilih sebagai informan melalui proses skrining PTSD. Data dikumpulkan melalui wawancara mendalam dan dianalisis menggunakan teknik coding dan interpretasi deskriptif. Hasil penelitian menunjukkan bahwa para informan mengalami berbagai bentuk trauma psikologis, seperti mimpi buruk, kecemasan, penghindaran terhadap ingatan bencana, serta perubahan cara pandang terhadap kehidupan dan bencana. Faktor penting yang membantu proses pemulihan trauma adalah dukungan keluarga serta pandangan positif terhadap pengalaman bencana. Temuan ini menegaskan pentingnya perhatian terhadap aspek psikologis penyintas bencana, khususnya remaja, guna mendukung proses pemulihan dan meningkatkan kesiapsiagaan menghadapi bencana di masa depan.